Adverse events associated with paediatric massage therapy: a systematic review - Hsing Jou; Sunita Vohra; Mohammad Karkhaneh; Liliane Zorzela; Martha Funabashi; Trish Dryden (BMJ Paediatrics Open)
Introduction Massage therapy (MT) is frequently used in children. No study has systematically assessed its safety in children and adolescents. We systematically review adverse events (AEs) associated with paediatric MT.Methods We searched seven electronic databases from inception to December 2018. We included studies if they (1) were primary studies published in a peer-reviewed journal, (2) involved children aged 0–18 years and (3) a type of MT was used for any indication. No restriction was applied to language, year of publication and study design. AEs were classified based on their severity and association to the intervention.Results Literature searches identified 12 286 citations, of which 938 citations were retrieved for full-text evaluation and 60 studies were included. In the included studies, 31 (51.6%) did not report any information on AEs, 13 (21.6%) reported that no AE occurred and 16 studies (26.6%) reported at least one AE after MT. There were 20 mild events (grade 1) that resolved with minimal intervention, 26 moderate events (grades 2–3) that required medical intervention, and 18 cases of severe AEs (grades 4–5) that resulted in hospital admission or prolongation of hospital stay; of these, 17 AEs were volvulus in premature infants, four of which were ultimately fatal events.Conclusion We identified a range of AEs associated with MT use, from mild to severe. Unfortunately, the majority of included studies did not report if an AE occurred or not, leading to publication bias. This review reports an association between abdominal massage with volvulus without malrotation in preterm infants; it is still to be defined if this is casual or not, but our findings warrant caution in the use of abdominal massage in preterm infants.